LEGAL ANALYSIS OF THE TRANSFORMATION OF ECONOMIC CRIMES IN THE DIGITAL ERA (CYBERCRIME) - Tri Wani Andini; Hudi Yusuf (Warmadewa Press, 2025)
The development of digital technology has brought significant changes in various aspects of human life, including in the economic sector. Digitalization has made transactions and economic activities easier, increased efficiency, and expanded access to the global market. However, this technological advancement has also given rise to new challenges, one of which is the increase in digital-based economic crimes or what is known as cybercrime. This research aims to (1) examine the impact of economic crimes in the digital era (cybercrime) on economic stability in Indonesia and (2) analyze the effectiveness of national legal regulations in dealing with economic crimes in the digital era (cybercrime). The research method used in this study is a normative research method with the data collection method used being library data or document studies (Library Research) sourced from legal materials in the form of primary legal materials, secondary legal materials and tertiary legal materials. The conclusion obtained from this study is that economic crimes in the digital era (cybercrime) are not only a criminal problem, but also threaten the stability of the Indonesian economy as a whole. National legal regulations have provided a framework for dealing with economic crimes in the digital era (cybercrime), but their effectiveness is still limited by less-than-optimal implementation, inadequate infrastructure, and lack of cross-country cooperation. Therefore, collaboration is needed between the government, private sector, and society in increasing digital literacy, strengthening regulations, and improving digital security systems to minimize the negative impacts of this digital economic crime.